2005
DOI: 10.1002/joc.1210
|View full text |Cite
|
Sign up to set email alerts
|

Temperature reconstructions and comparisons with instrumental data from a tree-ring network for the European Alps

Abstract: Ring-width and maximum latewood density data from a network of high-elevation sites distributed across the European Alps are used to reconstruct regional temperatures. The network integrates 53 ring-width and 31 density chronologies from stands of four species all located above 1500 m a.s.l. The development and basic climatic response patterns of this network are described elsewhere . The common temperature signal over the study region allowed regional reconstructions to be developed using principal component … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(92 citation statements)
references
References 44 publications
5
86
0
1
Order By: Relevance
“…As there are no neighboring stations with which to compare the early Sitka record, and these data were not included in the corrected GHCN record, we hypothesize that the problem may lie in the early instrumental data. Similar observations have also been made in Europe between dendroclimatic reconstructions and long early instrumental records (Hughes et al 1984;Bü ntgen et al 2005;Frank and Esper 2005;Wilson et al 2005).…”
Section: Calibration and Verification Of Goa January-september Tempersupporting
confidence: 83%
“…As there are no neighboring stations with which to compare the early Sitka record, and these data were not included in the corrected GHCN record, we hypothesize that the problem may lie in the early instrumental data. Similar observations have also been made in Europe between dendroclimatic reconstructions and long early instrumental records (Hughes et al 1984;Bü ntgen et al 2005;Frank and Esper 2005;Wilson et al 2005).…”
Section: Calibration and Verification Of Goa January-september Tempersupporting
confidence: 83%
“…Frank and Esper (2005) present comparisons between Alpine tree-ring based temperature reconstructions and instrumental data. They found that the response of ring-width data is not strictly limited to summer season temperatures, but also carries an annual signal particularly in the lower frequency domain (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The ring-width sequences from both sites were found to be highly correlated at this stage, indicative of a common climate signal. It has been suggested that tree-ring series growing within one site may show different climate-growth associations due to micro-environmental conditions (Frank and Esper 2005;Meko 1997;Wilmking et al 2005). For example, tree rings in shaded or concave locations with relatively abundant moisture availability in arid regions may be less sensitive to moisture.…”
Section: Tree-ring Chronologymentioning
confidence: 99%